2021
DOI: 10.1073/pnas.2112237118
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in the outer membrane of Escherichia coli

Abstract: Gram-negative bacteria are surrounded by a protective outer membrane (OM) with phospholipids in its inner leaflet and lipopolysaccharides (LPS) in its outer leaflet. The OM is also populated with many β-barrel outer-membrane proteins (OMPs), some of which have been shown to cluster into supramolecular assemblies. However, it remains unknown how abundant OMPs are organized across the entire bacterial surface and how this relates to the lipids in the membrane. Here, we reveal how the OM is organized from molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 62 publications
5
55
1
Order By: Relevance
“…This clearly contrasts with our work, where separate SusC or SusD components have never been observed during purification, regardless of whether the purification tag was located on SusC or SusD. Moreover, while it is not clear how much the E. coli OM resembles that of B. theta, recent work has shown that E. coli OMP and LPS mobility is limited 30,31 , raising questions regarding the efficiency of dynamically (dis)assembling transport complexes in a crowded OM.…”
Section: Discussioncontrasting
confidence: 96%
“…This clearly contrasts with our work, where separate SusC or SusD components have never been observed during purification, regardless of whether the purification tag was located on SusC or SusD. Moreover, while it is not clear how much the E. coli OM resembles that of B. theta, recent work has shown that E. coli OMP and LPS mobility is limited 30,31 , raising questions regarding the efficiency of dynamically (dis)assembling transport complexes in a crowded OM.…”
Section: Discussioncontrasting
confidence: 96%
“…The mechanism of action thus goes beyond a simple detergent-like effect as suggested previously 49 . Recent MD simulations of polymyxin-induced clusters 50 , 51 have proposed an increase in the local order of LPS bilayers by crystal domains in hexagonal coordination, which was also found to be correlated with the bacterial sensitivity to antimicrobials 52 , 53 . The crystalline structures identified in this work likely give a rationale for these observations.…”
Section: Discussionmentioning
confidence: 95%
“…OMPs are the major components of bacterial OMs, accounting for more than 50% of the OM volume 58,59 . The quantitative analysis of single-cell data suggest ~500 of molecules of OmpF need to be assembled into the outer membrane per minute per cell 60,61 , meaning that factors that promote the efficiency of OmpF assembly are critical to ensure that E. coli can handle this extraordinary rate of substrate protein flux. In order to fight against external insult, all of the Gram-negative bacteria contain BamD, the OMPs assembly accelerator.…”
Section: Discussionmentioning
confidence: 99%